Agglomeration economies and productivity in Indian industry - Lall, Somik V., 1972- 1972- (Policy research working paper, 2001)
The benefits to Indian manufacturing firms of locating in dense urban areas do not appear to offset the associated costs. Improving the quality and availability of transport infrastructure linking smaller urban areas to the rest of the interregional network would improve manufacturing plants' access to markets and would give standardized manufacturing activities a chance to move out of large, costly urban centers to lower cost secondary centers